New insights in novel Escherichia coli colistin resistant strains isolated from Argentina - Maturana, Patricia del Valle (2020)
Colistin is a polymyxin antibiotic (polymyxin E) that has in recent years re-emerged as an option for treatment of multidrug-resistant bacteria. Recently, the re-introduction of colistin resulted in the appearance of colistin-resistant bacteria, which is usually caused by LPS modifications. The fact that this modification is mediated by a plasmid carrying the mcr-1 gene, implies a horizontal transfer of colistin resistance. In Argentina, the National Reference Laboratory in Antimicrobial Resistance (NRLAR), has recently screened several bacteria for the MCR-1 plasmid, detecting nine Escherichia coli isolates carrying the plasmid with the mcr-1 gene, among others. In this context, we proposed to assess the effect of surface charge modifications induced by the plasmid MCR-1 and its impact on the resulting colistin resistance in two clinical isolates of colistin-resistant E. coli. Using zeta potential assays, we confirmed the reduction of negative charge exposure on clinical isolates compared to the reference strain of E. coli. In addition, through permeabilization assays, we were able to correlate this reduction in charge exposure with the extent of damage to the bacterial membrane. The fact that this surface charge modification through substitution of lipid A is plasmid encoded, represents an important concern for future antimicrobial peptide drug development.